Multitarget strategies in Alzheimer's disease: benefits and challenges on the road to therapeutics. (April 2016) - Rosini, Michela; Simoni, Elena; Caporaso, Roberta; Minarini, Anna
Alzheimer's disease is a multifactorial syndrome, for which effective cures are urgently needed. Seeking for enhanced therapeutic efficacy, multitarget drugs have been increasingly sought after over the last decades. They offer the attractive prospect of tackling intricate network effects, but with the benefits of a single-molecule therapy. Herein, we highlight relevant progress in the field, focusing on acetylcholinesterase inhibition and amyloid pathways as two pivotal features in multitarget design strategies. We also discuss the intertwined relationship between selected molecular targets and give a brief glimpse into the power of multitarget agents as pharmacological probes of Alzheimer's disease molecular mechanisms.